Meta-Milgram: an empirical synthesis of the obedience experiments. - Nick Haslam; Steve Loughnan; Gina Perry (PLoS ONE)
Milgram's famous experiment contained 23 small-sample conditions that elicited striking variations in obedient responding. A synthesis of these diverse conditions could clarify the factors that influence obedience in the Milgram paradigm. We assembled data from the 21 conditions (N = 740) in which obedience involved progression to maximum voltage (overall rate 43.6%) and coded these conditions on 14 properties pertaining to the learner, the teacher, the experimenter, the learner-teacher relation, the experimenter-teacher relation, and the experimental setting. Logistic regression analysis indicated that eight factors influenced the likelihood that teachers continued to the 450 volt shock: the experimenter's directiveness, legitimacy, and consistency; group pressure on the teacher to disobey; the indirectness, proximity, and intimacy of the relation between teacher and learner; and the distance between the teacher and the experimenter. Implications are discussed.